1996
DOI: 10.1111/j.1540-8159.1996.tb03183.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Acute and Long‐Term Clinical Performance of Two Single Lead Atrial Synchronous Ventricular (VDD) Pacemakers: Diagonally Arranged Bipolar Versus Closely Spaced Bipolar Ring Electrodes

Abstract: Floating P wave sensing can be derived from bipolar atrial electrodes with different electrode configurations, although the relative clinical efficacy of these methods of atrial sensing has not been studied. We evaluated 32 sex and age matched patients with advanced AV block who received AV synchronous pacers using either a single lead with diagonally arranged bipole (Unity VDDR, Model 292, Intermedics Inc.) or closely spaced bipolar complete ring electrodes (Thera VDD, Model 8948, Medtronic Inc.). The total s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 13 publications
(2 reference statements)
1
14
1
Order By: Relevance
“…5,[7][8][9] Overall incidence of AUS was 22%. In spite of some methodological differences and vigorousness in the assessment of AUS, our results are comparable to previous reports.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,[7][8][9] Overall incidence of AUS was 22%. In spite of some methodological differences and vigorousness in the assessment of AUS, our results are comparable to previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…8,12 In a study in which all the atrial sensitivities were programmed to the most sensitive levels, Hunziker et al reported that maximum programmable atrial sensitivity was a predictor of loss of AV synchrony. This was not surprising as it has been well known that the higher the programmed atrial sensitivity, the higher the atrial sensing capability.…”
Section: Pwa Usuallymentioning
confidence: 99%
“…Further studies will be required to compare the incidence of VDD versus DDD pacing in suppressing AF. (30) …”
Section: Ams In Vdd Pacemakersmentioning
confidence: 99%
“…Although reprogramming to a non-tracking mode (such as DVI, DDI or DDIR) prevents this clinical event, these modes do not provide appropriate AV synchrony if the sinus rate exceeds the programmed lower rate. (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37) Limitation of the upper tracking rate only partly addresses this problem and may compromise exercise capacity or lead to symptoms from pacemaker Wenckebach behaviour at relatively slow rates. In response to this clinical dilemma, a variety of mode-switching algorithms has been devised that are meant to prevent tracking of pathological atrial tachy-arrhythmias while allowing ventricular pacing that is synchronous with the atrial electrocardiogram during sinus rhythm [17][18][19].…”
Section: Wwwintechopencommentioning
confidence: 99%
“…[4][5][6] Today, multiple VDD pacing systems are on the market and their clinical performance is such that usually more than 98% of all beats are correctly sensed in the atrium and used for triggered ventricular pacing in patients with AV block. [7][8][9][10] Although the sensed atrial signals from floating electrodes are always smaller and more variable than signals from leads with fixed atrial wall contact, the mean P wave amplitudes remain very stable over time. In combination with dedicated VDD pulse generators that oVer a higher atrial sensitivity than conventional DDD pacemakers, the atrial sensing safety margins typically are 4-6 times higher than the corresponding atrial sensing threshold.…”
mentioning
confidence: 99%